CHILDREN'S LEGAL AND AUTHORITIES STATUS OF THE DEVOTIVE MARRIAGE RESULTS BECAUSE OF THE CANCELLATION OF MARRIAGE BASED ON REGULATION NO.1 YEAR 1974 AND ISLAMIC LAW COMPILATION IN INDONESIA - Aisyah Aisyah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to find out about the position of the child of the result of a broken marriage due to the existence of cancellation, and the inheritance position of a child who is a result of a broken marriage due to a marriage cancellation The method used in writing this Journal is a qualitative method with data collection techniques is library research collected and analyzed with descriptive techniques. The results of the study show that the Nasab position of a child who has a broken marriage due to a marriage cancellation is attributed to his father and mother, this is based on Article 28 of Law No. 1 of 1974 and Article 75 of the Compilation of Islamic Law affirms that the cancellation of a marriage based on a court decision does not apply retroactively to the children born from the marriage. The inheritance of a child who has a broken marriage due to a marriage cancellation can still inherit the property from his father or mother and also the child has a family relationship with the family of the father or mother. Keyword : Children's Legal And Authorities Status, The Devotive Marriage, Islamic Law      Compilation.